If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -2) = x + 3 Reorder the terms: 2(-2 + x) = x + 3 (-2 * 2 + x * 2) = x + 3 (-4 + 2x) = x + 3 Reorder the terms: -4 + 2x = 3 + x Solving -4 + 2x = 3 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -4 + 2x + -1x = 3 + x + -1x Combine like terms: 2x + -1x = 1x -4 + 1x = 3 + x + -1x Combine like terms: x + -1x = 0 -4 + 1x = 3 + 0 -4 + 1x = 3 Add '4' to each side of the equation. -4 + 4 + 1x = 3 + 4 Combine like terms: -4 + 4 = 0 0 + 1x = 3 + 4 1x = 3 + 4 Combine like terms: 3 + 4 = 7 1x = 7 Divide each side by '1'. x = 7 Simplifying x = 7
| y-1.5=1 | | 3x+2x+5=10(x+1) | | 891.25=x(7.5+4.75) | | 22+2s=10+5s | | 22+2s=1 | | -12=-2h+4-1.2h | | 3x-5x+6=12 | | 2(2x-14)=x+2 | | 5x+5=11x+15 | | 2m+45=-23 | | 6+5=0 | | 8(s+3)=7 | | -3(-4+4h)= | | 53x+14=43x+36 | | 30x=27x+11 | | 3w+116=500 | | 2(x+2)=x+10 | | x=10/0 | | 3(a-2)=4b+5 | | 3+-3(-2h+6)= | | 104=4(2-4x) | | x+41=70 | | 6[5-8(-4)]+12=x | | 6(-1+x)=-54 | | 891.25=7.5x+4.75y | | 0.80x+0.05(4-x)=0.10(-88) | | 11-3n=9n+2 | | 157=113-u | | 2(x+19)=x+29 | | 4+4x=x | | -9t+-7(-6+-10)= | | 2(x+9)=x+29 |